Publication trends and hotspots in enhanced recovery after surgery: 20-year bibliometric analysis. Issue 2 (12th December 2020) - Zhang, R; Qi, S; Dai, W; Chen, S; Zhang, Y; Tian, W; Yan, W; Kong, M; Tian, J; Su, D
Abstract : We evaluated enhanced recovery after surgery (ERAS) research and used bibliometric analysis to quantitatively and qualitatively predict research hotspots through extracting relevant publications from the core collection of the Web of Science database.